2020
DOI: 10.1111/opn.12309
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an end‐of‐life gerontological nursing education programme on the attitudes and knowledge of clinical nurses: A non‐randomised controlled trial

Abstract: Aims To evaluate how a structured interactive two‐day education programme for clinical nurses on end‐of‐life (EOL) care for older people affects nurses’ attitudes and knowledge. Design Non‐randomised controlled trial. Methods Nurses were recruited separately for intervention and control groups. The intervention group assisted older patients with EOL care and recruited patients for the programme. To prevent sampling bias, control group nurses were recruited from a facility with numerous EOL care opportunities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Other multicomponent intervention studies using education or training had also reported improvement of staff attitude toward end-of-life care [ 21 , 23 , 28 ]. As previous studies have suggested that education regarding end-of-life care improves attitudes towards it [ 45 , 46 ], end-of-life care education, which is one of the components of this tool, could have contributed to the improvement of nurses’ attitudes in this study.…”
Section: Discussionmentioning
confidence: 80%
“…Other multicomponent intervention studies using education or training had also reported improvement of staff attitude toward end-of-life care [ 21 , 23 , 28 ]. As previous studies have suggested that education regarding end-of-life care improves attitudes towards it [ 45 , 46 ], end-of-life care education, which is one of the components of this tool, could have contributed to the improvement of nurses’ attitudes in this study.…”
Section: Discussionmentioning
confidence: 80%
“…Additionally, nurses in these settings should emphasize their competence in pharmacotherapy [ 42 ]. For quality end-of-life care, a structured and evidence-based educational programme is recommended to nursing staff [ 30 , 43 ]. End-of-life care provision must be possible in settings such as hospitals, homes or community and rehabilitation placements [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The second trend is a willingness to collaborate with and to account for the needs of family members and informal caregivers. Because family members often become part of the healthcare team, nurses require skills and knowledge to involve family caregivers accordingly [30][31][32]. The third trend in gerontological nursing is a focus on health promotion and healthy ageing via disease prevention and a healthy lifestyle [28,33].…”
Section: Trends Analysismentioning
confidence: 99%